A Comparative Evaluation of Public Health Centers with Private Health Training Centers on Primary Healthcare Parameters in India: A Study by Data Envelopment Analysis Technique. - Davey, Sanjeev; Raghav, Santosh Kumar; Singh, Jai Vir; Davey, Anuradha; Singh, Nirankar (Indian Journal of Community Medicine)
Background: The evaluation of primary healthcare services provided by health training centers of a private medical college has not been studied in comparison with government health facilities in Indian context. Data envelopment analysis (DEA) is one such technique of operations research, which can be used on health facilities for identifying efficient operating practices and strategies for relatively efficient or inefficient health centers by calculating their efficiency scores. Materials and Methods: This study was carried out by DEA technique by using basic radial models (constant ratio to scale (CRS)) in linear programming via DEAOS free online Software among four decision making units (DMUs; by comparing efficiency of two private health centers of a private medical college of India with two public health centers) in district Muzaffarnagar of state Uttar Pradesh. The input and output records of all these health facilities (two from private and two from Government); for 6 months duration from 1st Jan 2014 to 1st July 2014 was taken for deciding their efficiency scores. Results: The efficiency scores of primary healthcare services in presence of doctors (100 vs 30%) and presence of health staff (100 vs 92%) were significantly better from government health facilities as compared to private health facilities (P < 0.0001). Conclusions: The evaluation of primary healthcare services delivery by DEA technique reveals that the government health facilities group were more efficient in delivery of primary healthcare services as compared to private training health facilities group, which can be further clarified in by more in-depth studies in future.